Multi-suspension and multi-functional facility and device used for carrying child - JIN YANDONG (2017)
The invention relates to a multi-suspension and multi-functional facility and device used for carrying a child, in particular to a foldable baby stroller. Frames, wheels mounted on the frames, and a sitting and lying device allowing an infant to sit and lie down are included. The sitting and lying device is provided with a limiting device, and the limiting device can limit relative rotation of a first seat support and a second seat support when the first seat support and the second seat support rotate to form a plane. The sitting and lying device is provided with two dismounting and mounting ports. The two sides of the sitting and lying device are hinged to the frames through at least two connecting rod assemblies correspondingly. The frames include the first frame and the second frame which are hinged together. The sitting and lying device is formed by sequentially hinging one end of the first seat support, a seat inner-left connecting rod, a seat outer-left connecting rod and one end of the second seat supp